Construct validity in cross-cultural, developmental research: challenges and strategies for improvement - Nicole J. Wen; Dorsa Amir; Jennifer M. Clegg; Helen E. Davis; Natalia B. Dutra; Michelle A. Kline; Sheina Lew-Levy; Tanya MacGillivray; Gairan Pamei; Yitong Wang; Jing Xu; Bruce S. Rawlings (Evolutionary Human Sciences)
The recent expansion of cross-cultural research in the social sciences has led to increased discourse on methodological issues involved when studying culturally diverse populations. However, discussions have largely overlooked the challenges of construct validity – ensuring instruments are measuring what they are intended to – in diverse cultural contexts, particularly in developmental research. We contend that cross-cultural developmental research poses distinct problems for ensuring high construct validity owing to the nuances of working with children, and that the standard approach of transporting protocols designed and validated in one population to another risks low construct validity. Drawing upon our own and others’ work, we highlight several challenges to construct validity in the field of cross-cultural developmental research, including (1) lack of cultural and contextual knowledge, (2) dissociating developmental and cultural theory and methods, (3) lack of causal frameworks, (4) superficial and short-term partnerships and collaborations, and (5) culturally inappropriate tools and tests. We provide guidelines for addressing these challenges, including (1) using ethnographic and observational approaches, (2) developing evidence-based causal frameworks, (3) conducting community-engaged and collaborative research, and (4) the application of culture-specific refinements and training. We discuss the need to balance methodological consistency with culture-specific refinements to improve construct validity in cross-cultural developmental research.